2002
DOI: 10.1139/z02-125
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural observations on rodlet-cell development in the head kidney of the southern platyfish, Xiphophorus maculatus (Teleostei: Poeciliidae)

Abstract: The enigmatic rodlet cell has been observed in tissues of marine and freshwater teleosts. The origin and function of this cell remain unclear. We describe the association of the rodlet cell with the head-kidney tissue of the southern platyfish, Xiphophorus maculatus. We have observed rodlet cells in various tissues of X. maculatus, e.g., the hemopoietic compartments of the head kidney, gill epithelia, and ovarian tissue, and in melanotic tumors. Recently, we found rodlet cells within the mesothelium and muscul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
43
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 23 publications
7
43
1
Order By: Relevance
“…In a previous study, Kramer and Potter [17] reported that the development of cellular junctions such as desmosomes was related with the absence of the apical fibrous layer and the cell capability to release the rodlets. Moreover, rodlet cells located in extra-epithelial sites, and therefore unrelated with cellular junctions, are not able to discharge the rodlets [17].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, Kramer and Potter [17] reported that the development of cellular junctions such as desmosomes was related with the absence of the apical fibrous layer and the cell capability to release the rodlets. Moreover, rodlet cells located in extra-epithelial sites, and therefore unrelated with cellular junctions, are not able to discharge the rodlets [17].…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, Kramer and Potter [17] reported that the development of cellular junctions such as desmosomes was related with the absence of the apical fibrous layer and the cell capability to release the rodlets. Moreover, rodlet cells located in extra-epithelial sites, and therefore unrelated with cellular junctions, are not able to discharge the rodlets [17]. In line with this result, Bielek [1] left open the debate about the apparent contradictory existence of cellular junctions in cells that share functional properties with leucocytes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Of the papers published on RCs, the majority refer to the mature cell stage; nevertheless, putative immature and developmental RC stages have been described in several accounts (Iger & Abraham, 1997; Dezfuli et al ., 1998; Kramer & Potter, 2002). Immature RCs are oval in shape with large, pale euchromatic nuclei, conspicuous rough endoplasmic reticula and peculiar small, elongated mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, a longstanding controversy exists in the literature regarding the origin and nature of RCs. Although the exogenous hypothesis considers them as parasites (Bannister,1966; Barber,1979; Bielek and Viehberger,1983; Mayberry et al,1979; Richards et al,1994; Viehberger and Bielek,1982), the endogenous hypothesis regards them as normal constituent of fishes animal tissue, with a potential secretory activity (Bielek,2005; Dezfuli et al,1998, 2000, 2002,2003a, b; Leino,1974, 1982, 1996; Kramer and Potter,2002; Manera et al,2001; Mazon et al,2007; Vigliano et al,2006). Several evidence over recent years have supported the hypothesis that the RC participates in the fish non‐specific immune response (Abraham et al,2001; Dezfuli et al,1998, 2000, 2003a; Leino,1996; Reite,1997; Reite and Evensen,2006 ; Sulimanovic et al,1996).…”
Section: Introductionmentioning
confidence: 99%